2022
DOI: 10.1080/07853890.2022.2077428
|View full text |Cite
|
Sign up to set email alerts
|

Soluble klotho as an effective biomarker to characterize inflammatory states

Abstract: Background & Aims Soluble α-Klotho (s-Klotho) is a circulating protein with pleiotropic effects that mainly induce protective effects. Our study investigates the associations between s-Klotho and several established inflammatory biomarkers, with the aim of examining whether s-Klotho levels are representative of inflammatory states. Methods A total of 11,128 eligible participants from NHANES 2007–2016 were included in our study. Levels of four inflammatory biomarkers, ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…In the latest studies, soluble α-Klotho has been shown to be significantly associated with well-recognized inflammatory biomarkers, e.g., uric acid (UA) [ 30 , 31 ], C-reactive protein (CRP), white blood cell (WBC) count, and mean platelet volume (MPV) [ 31 ]. In PD patients, high concentrations of Klotho (above the median value of 329 pg/mL) were associated with lower IL-6 levels [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the latest studies, soluble α-Klotho has been shown to be significantly associated with well-recognized inflammatory biomarkers, e.g., uric acid (UA) [ 30 , 31 ], C-reactive protein (CRP), white blood cell (WBC) count, and mean platelet volume (MPV) [ 31 ]. In PD patients, high concentrations of Klotho (above the median value of 329 pg/mL) were associated with lower IL-6 levels [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Martín-Núñez et al found that reduced levels of S-Klotho were associated with the proinflammatory status, such as higher ratio of tumor necrosis factor-alpha/interleukin-10 and the C-reactive protein level [ 27 ]. Wu et al also demonstrated that the serum levels of S-Klotho were significantly and inversely associated with four well-recognized inflammation-related biomarkers (white blood cell count, mean platelet volume, C-reactive protein, and uric acid) in the cohort [ 28 ]. Several experimental models demonstrated that upregulation of endogenous Klotho or exogenous administration of Klotho both could suppress renal fibrosis and maintain kidney function in chronic kidney disease [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also important to note that many studies show a positive correlation between s-Klotho and markers of health and biological age [128][129], also in patients with various disorders [130].…”
Section: Discussionmentioning
confidence: 99%